2015
DOI: 10.1016/j.tem.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac contraction-induced GLUT4 translocation requires dual signaling input

Abstract: Contraction-induced translocation of glucose transporter type-4 (GLUT4) to the sarcolemma is essential to stimulate cardiac glucose uptake during increased energy demand. As such, this process is a target for therapeutic strategies aiming at increasing glucose uptake in insulin-resistant and/or diabetic hearts. AMP-activated protein kinase (AMPK) and its upstream kinases form part of a signaling axis essential for contraction-induced GLUT4 translocation. Recently, activation of protein kinase-D1 (PKD1) was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 64 publications
0
31
0
Order By: Relevance
“…GLUT4 capacity (amount at the plasma membrane) is critically and rapidly regulated by insulin with additional impact made by muscle contraction [21,22]. Thus the presence and type of glucose transporter is critical.…”
Section: Eric Arthur Newsholme's Studies: the Basis Of Regulation In mentioning
confidence: 99%
“…GLUT4 capacity (amount at the plasma membrane) is critically and rapidly regulated by insulin with additional impact made by muscle contraction [21,22]. Thus the presence and type of glucose transporter is critical.…”
Section: Eric Arthur Newsholme's Studies: the Basis Of Regulation In mentioning
confidence: 99%
“…In cardiac tissue the expression of GLUT4 is four times higher than that of GLUT1 [29]. Cardiac tissue primarily utilizes GLUT4 for its glucose uptake, but in diabetic patients there is a decrease in expression of GLUT4 and therefore a decrease in the uptake and utilization of glucose.…”
Section: Cellular Uptake and Utilization Of Molecular Fuelsmentioning
confidence: 99%
“…A reduced expression of the insulin-regulated glucose transporter type-4 (GLUT4) isoform, which in itself plays an essential role in blood glucose regulation by transporting and mediating glucose uptake, 36 is purported to be a causative factor leading to insulin resistance and subsequent diabetic complications. 37 As the effect of physical activity on glycemic control and body composition is well documented, 34,38 exercise training could be used as a first line of treatment for type 2 diabetes, and numerous studies have also showed the efficacy of HIIT [39][40][41] and MICT 42,43 with regards to the effective management of the condition.…”
Section: Insulin Sensitivitymentioning
confidence: 99%